THE POTENTIAL APPLICATIONS OF US MRNA VACCINES IN CHINA AND IMPLICATIONS FOR A “UNIVERSAL” COVID VACCINE: Received: 25th August 2023; Revised: 02nd November 2023, 28th November 2023; Accepted: 12th December 2023 - Xiang, Nan (LIFE: International Journal of Health and Life-Sciences, 2023)
The resurgence of Covid outbreak in China at the start of 2023 with the new XBB variants made people question the effectiveness of the Sinopharm vaccine. In this paper, I tried to investigate the applicability of the US mRNA vaccinations in the Chinese population, and the implication of the development of a universal Covid vaccine. I blasted the selected BA.2.12.1 strain’s genome and spike protein sequences of China’s, Japan’s and the US’s (NY, CA, WA and AZ) strains from the NCBI SARS-CoV-2 database. Blast results showed a high percentage (>0.95) of alignment among the complete genome and spike protein sequences from all the selected regions, which supported the ideas of the applications of one mRNA vaccine to target the dominant strain in different countries. On the other hand, the identification of certain point mutations (R343T, G679R) in the functional and structural part of the spike protein underlined the high mutability of the virus as it spreads across continents. These findings suggested that while mRNA vaccines could be more effective for the prevailing strain in China and potentially the rest of the world, in order to make a firm conclusion and medical plan for the implementation, it still required additional trials and research with more data.